Peningkatan Kepatuhan Pencegahan Penularan Covid-19 Pada Ibu Hamil Dengan Edukasi Online (Via WhatsApps) di Kecamatan Kwanyar Kabupaten Bangkalan - Merlyna Suryaningsih; Qurrotu Aini (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Pregnant women are listed as one of the vulnerable groups at risk of being infected with COVID-19, due to physiological changes during pregnancy that result in a decrease in partial immunity. In the initial study conducted before the activity, it was found that there were still many pregnant women when they were outside the home that did not comply with health protocols such as not wearing a mask, still talking to neighbors without keeping their distance, and occasionally appearing to still join the crowd. The purpose of this study was to analyze the Effect of Online Education (Via WhatsApps) on Compliance with the Prevention of Covid-19 Transmission in Pregnant Women in Kwanyar District, Bangkalan Regency. The design of this study was a quasi-experimental pretest posttest design. Independent Variabel is Online Education and dependent variable is Compliance For Prevention of COVID-19 Transmission The number of samples was 54 respondents from pregnant women in Gunung Siring village, Kwanyar district, with a total sample of 27 respondents from the control group and 27 respondents from the treatment group, which were taken using purposive sampling technique. The research instrument used a questionnaire. Statistical test using wilcoxon and Mann Whitney with = 0.05. The results showed that there was a difference in the mean between the control and treatment groups, so it can be concluded that there is an effect of online education on increasing the compliance of pregnant women in preventing the transmission of COVID-19.